Beyond silos: Drivers and barriers to intersectoral collaboration in zoonotic disease surveillance and response in the Greater Accra Metropolitan Area, Ghana - Joannishka K. Dsani; Sherry Ama Mawuko Johnson; Sandul Yasobant; Walter Bruchhausen (PLoS ONE, 2026)
The One Health approach has gained global traction as a strategy to combat zoonotic diseases, which account for 60–75% of emerging infectious diseases. While effective surveillance requires intersectoral collaboration, challenges such as fragmented systems, resource constraints, and weak coordination hinder efforts, particularly in low- and middle-income countries like Ghana. This qualitative study explores the factors influencing collaboration in zoonotic disease surveillance and response at the operational level, providing insights to strengthen intersectoral collaboration and improve public health outcomes across human, animal and wildlife sectors. Using reflexive thematic analysis, we analyzed interviews with 66 professionals from the human, animal, and wildlife health sectors, all directly involved in zoonotic disease surveillance and response. The findings reveal individual factors (interpersonal relationships, personal initiative, motivations, professional hierarchy, shared interests) and structural factors (financial resources, workforce availability, the governance and organization of surveillance and response systems, institutional visibility, knowledge systems) that shape collaboration dynamics. Additionally, positive outcomes from past collaborations created reinforcing cycles that influenced future engagement. Participants shared expectations of improved efficiency, strengthened disease surveillance, and enhanced resource pooling from future collaboration. Despite the global push for intersectoral collaboration, operational-level challenges persist. While grounded in a Ghanaian context, the types of factors identified likely resonate across resource-limited settings, though their specific manifestations and relative importance may vary by context. These findings underscore the broader need for stronger governance, equitable partnerships, and realistic alignment of stakeholder expectations to foster sustainable One Health collaboration and enhance zoonotic disease surveillance globally.